Analysis of the impact of various gamification factors on the level of player satisfaction - Demidiuk, Krystian; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2022)
Gamification has become a very popular term for a wide range of opportunities to increase customer interest and satisfaction. This has many uses, including science, commerce and everyday life. Despite the widespread use of gamification mechanisms, the scale of possible benefits is still unknown. The following work examines the influence of various gamification factors on a player’s playing time and satisfaction in order to find the factor that brings the greatest benefit. The research was carried out using a game specially created for this purpose and on the basis of the results of the survey presented to the players. The results show that the five selected gamification factors are the challenges and the badges awarded for them have the greatest impact on both examined metrics.